Excessive daytime sleepiness in Parkinson's disease as assessed by Epworth Sleepiness Scale (ESS) - Kumar, Suresh; Bhatia, M; Behari, M (Sleep medicine, 2003)
Objective: To assess daytime sleepiness in patients with Parkinson's disease (PD) using the Epworth Sleepiness Scale (ESS). Material and methods: One hundred and forty-nine patients with PD (126 men, 23 women) and 115 age matched controls recruited from relatives of medical staff or spouses and other family members accompanying patients to the Movement Disorder Clinic of the All India Institute of Medical Sciences in New Delhi were included in the study. An ESS score of ≥8 was considered abnormal. Data obtained were analyzed using Chi square test for categorical variables and Student's t-test for continuous variables. Results: The mean age of patients with PD was 58.37 (S.D.=10.45) years, and that of controls 56.50 (S.D.=11.45) years, with a mean duration of disease of 5.68 (S.D.=3.85) years. The mean ESS score was 4.9 (S.D.=3.63) and 2.17 (S.D.=2.54) in PD patients and controls, respectively ( P<0.05). Thirty-two patients with PD (21%) had an ESS score of >8 whereas only 3% of controls scored ≥8 on the ESS ( P<0.05). Higher ESS scores were associated with a higher Hoehn and Yahr (H&Y) stage of disease and higher Unified Parkinson's Disease Rating Scale (UPDRS) (part I, III and total) scores ( P<0.019, P<0.013 and P<0.011, respectively). Conclusion: Excessive daytime sleepiness was more common in PD patients as compared to controls. Higher ESS scores correlated significantly with higher H&Y stage and higher UPDRS (part I, III and total) scores.